Konflik dan Ujaran Kebencian di Twitter (Studi Tentang Hashtag #2019TetapJokowi and #2019GantiPresiden Periode Januari-Februari 2019) - Anni’mah Nurul F; Nurhadi Nurhadi; Sigit Pranawa (Universitas Negeri Medan, 2020)
This research aims at understanding and explaing conflicts that take place in the virtual world. Twitter is chosen as a sample because it is one of the most widely used social media many so-called netizens use both for positive and negative purposes. One of the negative effects that twitter brings about is rampant hate speech. Data is collected by shooting screen that contain hashtag #2019gantipresiden and #2019tetapjokowi. Perspective used in this research is Lewis Coser’s conflict theory. Unlike other researches that focus on the impact of internet-mediated interaction, this reseach offers a new perspective that considers virtual world a space where each individual interacting in it gets involved in a negotiation process with other individual or a group of individuals. Conclusions drawn from this reseach are as follows : (1) if it comes to conflict, the nature of virtual - real worlds relation is diadic one; (2) things that occur in the virtual world can be managed to be realized in the real world and vice versa; (3) virtual world is an imaginary space constructed by groups of individuals due to interaction barrier in the real world.